A preliminary study of the effects of stimulant medications on estimates of psycholinguistic abilities for children with attention-deficit/hyperactivity disorder. - Redmond, Sean M.; Ash, Andrea C.; Zhang, Yue (Clinical Linguistics & Phonetics, 2024)
Underlying deficits in inattention, hyperactivity, and/or impulsivity might contribute to suboptimal test-taking behaviours during language assessments that can lead to diagnostic errors. Considerations of potential medication effects on estimates of children's nonword repetition, sentence recall, tense-marking, and narrative abilities are warranted given long-standing enthusiasm for these indices to serve as clinical markers for developmental language disorder (DLD). A battery consisting of 1 nonverbal, 1 reading, and 6 verbal measures was administered twice to 26 children (6–9 years) with independently diagnosed combined-type attention-deficit/hyperactivity disorder (ADHD). All participants had been prescribed stimulant medications for the management of their ADHD symptoms and were assessed off- and on-medication, with order counter-balanced across participants. Half of the participants had concomitant DLD. Examiners were unaware of children's clinical status during assessments or when they were testing children who had received medication. Effect sizes were calculated for each measure. Significant score differences indicating a beneficial impact of stimulant medications on children's performances were observed on the recalling sentences subtest of the Clinical Evaluation of Language Fundamentals and the Picture Peabody Vocabulary Test. Adjustments may be needed when speech language pathologists use sentence recall or receptive vocabulary measures to make diagnostic decisions with children who have ADHD.